Mean platelet volume in asymptomatic chorioamnionitis-exposed infants. A retrospective case-control study - Atef Alshafei; Moustafa Hassan; Yaser El saba; Anwar Khan; Mahmoud Ahmed (Hygeia Press di Corridori Marinella, 2020)
Introduction: Maternal chorioamnionitis (CA) is a serious condition causing several neonatal morbidities and long-term neurodevelopmental sequelae in exposed infants. Current guidelines still recommend admission, laboratory evaluation, and antibiotic administration to all CA-exposed infants. The incidence of early-onset neonatal sepsis (EOS) is currently low, owing to the routine intrapartum antibiotic administration to mothers identified to be at risk of developing CA. New diagnostic tools for early diagnosis of sepsis in apparently healthy infants exposed to maternal CA are needed. Previous studies showed that mean platelet volume (MPV) is evolving as a potential inflammatory marker of neonatal sepsis. We aimed to study whether MPV can be used as an adjuvant diagnostic tool for EOS in asymptomatic CA-exposed infants. Objective: To evaluate the role of MPV as an adjuvant biomarker of EOS in cases of asymptomatic CA-exposed infants. Design: Retrospective case-control study. Setting: A tertiary care Neonatal Intensive Care Unit (NICU). Patients: Asymptomatic CA-exposed infants 37-40 weeks of gestation admitted between May 2016 and April 2019 to the NICU of Dubai Hospital, UAE. Results: A total of 1,300 infants were admitted to NICU during the study period. Fifty-eight infants were included in the CA-exposed group and met the inclusion criteria, and 63 infants were matched as controls. No statistically significant differences were found in the MPV between the CA-exposed infants' group and the control group. Similarly, no significant differences were noted in total white blood cell count, platelet count, and absolute neutrophil count between the two study groups. Inflammatory markers were significantly elevated in the CA-exposed group; however, blood cultures were sterile in all included infants. Conclusions: MPV is not a sensitive marker of EOS in asymptomatic CA-exposed infants whose mothers received intrapartum antibiotic prophylaxis.